Growth sites and growth mechanisms at risk in cleft lip and palate - Friede, H (Acta odontologica Scandinavica, 1998)
A newborn with some kind of facial cleft displays certain characteristics of the nose, upper lip, and jaw caused by abnormal influence on specific growth sites and growth mechanisms. Treatment, particularly surgery, attempts to counteract this aberrant development, for both functional and aesthetic reasons. However, not infrequently, therapy impedes future midfacial growth to a greater or lesser degree. To better understand the varying growth influence, this article aims to review certain aspects of growth of the middle third of the face in both normal and cleft subjects. The normal elongation of the maxilla, to give space for the molars, is usually not affected by lip surgery but rather by scar tissue from palatal repair. The displacement of the upper jaw in relation to the vomer is recognized. Early surgery should therefore avoid affecting the growth of the vomero-(pre)maxillary suture if possible. Periosteal growth, necessary for the development of dentoalveolar structures, might be affected by scar tissue from palatal repair. Different ways to reduce the development of palatal scars and their negative effects on growth are discussed.